Enhancement of CRF-PEEK osseointegration by plasma-sprayed hydroxyapatite: A rabbit model. (August 2014) - Suska, Felicia; Omar, Omar; Emanuelsson, Lena; Taylor, Mark; Gruner, Philipp; Kinbrum, Amy; Hunt, Duncan; Hunt, Trevor; Taylor, Andy; Palmquist, Anders
Carbon-fibre-reinforced polyether ether ketone (CFR-PEEK) exhibits excellent biomechanical properties as it has an elastic modulus similar to bone. However, CFR-PEEK displays inferior biocompatibility compared with titanium alloy and coating techniques are therefore of interest in order to improve integration. In this paper, the early biological response to CFR-PEEK implants, with and without hydroxyapatite coating, was investigated. Furthermore, a hydroxyapatite-coated titanium alloy reference served as a clinically relevant control. The study was conducted in a rabbit model, both in femur trabecular bone as well as in tibia cortical bone. The results demonstrated that an hydroxyapatite coating significantly enhances the bone response to PEEK implants in vivo. Moreover, in cortical bone, hydroxyapatite-coated PEEK implants induced superior bone response compared with hydroxyapatite-coated Ti ones. These results suggest that hydroxyapatite-coated CFR-PEEK is a suitable material for in vivo implantation.